2002
DOI: 10.1001/archderm.138.8.1071
|View full text |Cite
|
Sign up to set email alerts
|

UV-B Phototherapy Clears Psoriasis Through Local Effects

Abstract: Objective: To determine if UV-B phototherapy clears psoriasis through systemic effects.Design: Randomized, within-subject comparison of change in psoriasis in 3 plaques in patients attending for whole-body UV-B therapy. Change in patients' psoriasis plaques covered during UV-B treatment was compared with plaques in an untreated control group.Setting: University hospital phototherapy unit. Patients:The study population comprised 17 patients with chronic plaque psoriasis treated with UV-B and 24 psoriasis contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 24 publications
0
28
1
Order By: Relevance
“…In such studies it is possible that the effect of treatment on one side is transmitted to the other, thereby minimizing the difference between the 2 sides, but any such effect is likely to be small. 18 One of these studies 2 found slight differences in favor of PUVA, but they were not statistically significant. Another study, 3 in which bath PUVA was used, showed a higher clearance rate with NB-UVB, although the median number of treatments to clearance was lower in the PUVA group.…”
Section: Commentmentioning
confidence: 96%
“…In such studies it is possible that the effect of treatment on one side is transmitted to the other, thereby minimizing the difference between the 2 sides, but any such effect is likely to be small. 18 One of these studies 2 found slight differences in favor of PUVA, but they were not statistically significant. Another study, 3 in which bath PUVA was used, showed a higher clearance rate with NB-UVB, although the median number of treatments to clearance was lower in the PUVA group.…”
Section: Commentmentioning
confidence: 96%
“…In the case of psoriasis, nUVB seems to clear plaques through local rather than systemic effects, as unexposed plaques cleared significantly less than directly exposed plaques (35). However, it has also been hypothesized that clearing of psoriasis is a combination of local and systemic effects (36).…”
Section: Induction Of Dna Damagementioning
confidence: 99%
“…Several clinical trials have determined that the systemic effects of UVB therapy are unlikely to be of clinical importance in patients with or without HCV, but potential long-term effects have yet to be uncovered. [21][22][23] Psoralen plus UVA Another phototherapy, which includes the combination of exposure to UVA and ingestion of a psoralen photosensitizer, has shown to induce a longer remission period of disease. No studies have been done in patients with psoriasis and HCV receiving PUVA.…”
Section: Ultraviolet Bmentioning
confidence: 99%